Building Legal Aid Services from the Ground Up : Learning from Pilot Initiatives in Jordan - Prettitore, Paul Scott (World Bank, Washington, DC, 2014)
Like most governments, the Government of Jordan (GoJ) struggles with the provision of legal aid services, information, counseling and representation by a lawyer - to the poor. Jordanians have the legal right to state-sponsored services only for serious criminal cases, while the Jordan Bar Association tries to provide services for lesser crimes and civil cases. Civil Society Organizations (CSOs) have joined the pool of service providers. Yet legal aid remains much underutilized despite high demand, especially for family law (personal status) cases. These include divorce, alimony, child support and inheritance. The Jordanian CSO the Justice Center for Legal Aid (JCLA) provides legal aid via centers throughout Jordan, providing information and awareness to over 6,500 beneficiaries, counseling to 2,000 and legal representation to over 1,200 over the last several years.